THE IMPACT OF SOCIAL NETWORKING PLATFORMS ON FIRM INTERNATIONALIZATION: A CONCEPTUAL MODEL DEVELOPMENT (Third Sector Social Economic Review, 2023)
This paper develops a conceptual model that explains the relationship between the use of social networking platforms (SNPs) and firm internationalization. The model critically explores the network-based internationalization literature and explains how networks developed through SNPs can facilitate firm internationalization. Although the extant literature has investigated the role of network relationships, earlier studies have mostly focused on business and inter-personal relationships. However, with the rise of the internet, we have witnessed an exponential growth in the use of online social networks by internationalizing firms to access foreign markets. While previous research shed lights on the role of networks at broad level, they offer limited understanding on the idiosyncratic characteristics of online networks and their unique contribution to firm internationalization. Building on this gap, the present study makes a timely contribution to the literature by developing a conceptual model, which explains how and through which mechanisms online networks can facilitate firm internationalization. The interaction between online networks and firm internationalization is critically explained with five propositions. As social networks are becoming an important component of international business activities, this study creates opportunities for future studies, which aims to empirically test the relationship between social networks and firm internationalization.
Keywords: Internationalization; social networking platforms; social networks; network resources; global strategy.